The Motive of Metamorphosis in Victor Pelevin‘s Novel “Omon Ra” - Охняк, Магдалена (Literatūra, 2016)
In this article, the author analyses the motive of metamorphosis that is present in the novel entitled “Omon Ra” and in all of Victor Pelevin’s works. This motive is observed in the novel on different levels of text organisation and with different intensity. It is also combined with different literary devices and motives. Going deeper into the plot of the novel, the reader observes changes in the world depicted, but also physical and spiritual changes of the main character. This character transforms from a young dreamer into an obedient cosmonaut who would eagerly sacrifice his life for an idea (conquest of space). Thanks to an accident that saves him from committing suicide, he has an opportunity to choose a new way of life: either remaining in his past that is full of lies or rather choosing an unknown future. But at the end of the novel the author does not reveal the decision made by the protagonist. Thus, the author shows the reader that these are the novel’s main messages: the process of gradually maturing to a point where a decision can be made, the ability to transform, and the ability to cope in a boundary situation.